2017
DOI: 10.1097/mpg.0000000000001342
|View full text |Cite
|
Sign up to set email alerts
|

Risk Categorization Predicts Disability in Pain‐associated Functional Gastrointestinal Disorders After 6 Months

Abstract: Introduction For a large portion of youth, pain-associated functional gastrointestinal disorders (FGIDs) are associated with significant impairment over time. Clinically feasible methods to categorize youth with FGIDs at greatest risk for persistent pain-related impairment have not yet been identified. Methods Measures of functional disability, pain intensity and anxiety were collected on 99 patients with FGIDs (ages 8–18) during a visit to a pediatric gastroenterology office to assess for the presence of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…We also found that increased child anxiety was related to higher levels of child functional disability. Our finding is consistent with previous research demonstrating that anxiety symptoms in pediatric FAPD are associated with pain-related disability [18,28,29]. Indeed, youth with recurrent abdominal pain conditions such as FAPD show decreased participation in daily activities (e.g., school attendance decreases, less participation in hobbies, etc.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also found that increased child anxiety was related to higher levels of child functional disability. Our finding is consistent with previous research demonstrating that anxiety symptoms in pediatric FAPD are associated with pain-related disability [18,28,29]. Indeed, youth with recurrent abdominal pain conditions such as FAPD show decreased participation in daily activities (e.g., school attendance decreases, less participation in hobbies, etc.…”
Section: Discussionsupporting
confidence: 92%
“…Total scores range from 0 to 82, with higher scores reflecting greater levels of anxiety. A score of 25 or greater is considered clinically elevated anxiety, and elevated SCARED scores, in general, are associated with increased pain and disability in youth with FAPD [28,29]. The internal consistency of the SCARED for the current sample was 0.94, which is considered excellent.…”
Section: Child Fapd and Associated Symptoms Measuresmentioning
confidence: 73%
See 3 more Smart Citations